1924
DOI: 10.1172/jci100005
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of the Circulation of the Blood in Normal Resting Individuals *

Abstract: This paper describes two allied methods for the determination of the rate of blood flow which have yielded consistently reproducible results in untrained subjects. The data obtained in forty experiments on twenty-one normal resting individuals are presented in tabular form. The first method is suitable for use with subjects having practically any type of pathology but in the resting condition only. The second method is inapplicable when the subject has a pulmonary lesion preventing ventilation of part of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1926
1926
1935
1935

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 3 publications
(4 reference statements)
1
12
0
Order By: Relevance
“…Reliable current methods such as those devised by Plesch (1909); Krogh and Lindhard (1912); Douglas and Haldane (1922) ;Field, Bock, Gildea and Lathrop (1924); Burwell and Robinson (1924); all depend upon equilibrium between a gas or gases in the alveolar air and those in the pulmonary capillaries. Under the conditions imposed by pulmonary congestion such an equilibrium may be impossible to attain (Peters and Barr (1921)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliable current methods such as those devised by Plesch (1909); Krogh and Lindhard (1912); Douglas and Haldane (1922) ;Field, Bock, Gildea and Lathrop (1924); Burwell and Robinson (1924); all depend upon equilibrium between a gas or gases in the alveolar air and those in the pulmonary capillaries. Under the conditions imposed by pulmonary congestion such an equilibrium may be impossible to attain (Peters and Barr (1921)).…”
Section: Discussionmentioning
confidence: 99%
“…During the studies, observations were also made of changes in "basal" pulse rate and other changes were recorded. The output of the heart was measured by the method of Field, Bock, Gildea and Lathrop (1924), a method which requires no punctures of blood vessels and therefore lends itself to repeated application to the same subject. It involves the determination by respiratory methods of the carbon dioxide tension in the blood entering and leaving the lungs, and the measurement of the total gas exchange by the gasometer method.…”
Section: Introductionmentioning
confidence: 99%
“…The observations here reported were made by the method of Field, Bock, Gildea and Lathrop (10) with careful attention to the constancy of "standard basal" conditions as described in previous publications (11). In each case, observations were made only after several days of rest in hospital had led to the establishment of a relatively fixed level of bood pressure.…”
Section: Methodsmentioning
confidence: 99%
“…In 1922 Douglas and Haldane (3) showed that the same arteriovenous differences in CO2 content were obtained in a given subject, whether the rebreathing procedure equilibrated CO2 tensions only and oxygenated the blood in the lungs, or whether this procedure equilibrated simultaneously both CO2 and oxygen tensions of incoming venous blood with the rebreathed air. Field, Bock, Gildea, and Lathrop (4) showed that arterial blood drawn during the course of rebreathing a mixture of 6 per cent CO2 and 94 per cent oxygen was fully oxygenated, and that the CO2 tensions in arterial blood and in the rebreathed air were the same. Most workers have been able to demonstrate an equilibrium of CO2 tensions by similar rebreathing technique; Hamilton, Moore and Kinsman (5), however, were unable to establish equilibrium or " plateau " levels of CO2 during rebreathing in experiments with a small number of subjects.…”
mentioning
confidence: 98%